Cognition and performance: anxiety, mood and perceived exertion among Ironman triathletes. Issue 14 (11th June 2010) - Parry, David; Chinnasamy, Camilla; Papadopoulou, Eleni; Noakes, Timothy; Micklewright, Dominic
Abstract : Objective: The authors examined the changing patterns of mood before and after an Ironman triathlon, and the relationships between expected performance outcomes, perception of effort and pacing. Design: Twelve participants in the 2008 Ironman Austria triathlon competition were studied before, during and after the event. Each participant completed measures of mood, anxiety and perceived exertion, while pacing was calculated from official race timings at various points on the course. Results: Positive correlations were found between distance covered and rating of perceived exertion (RPE) during each of the individual disciplines, and also between RPE and the percentage of overall race time completed (r=0.826, p<0.001). A negative correlation was found between average speed and distance covered during the run segment (r=−0.911, p<0.005) with pace gradually declining. Differences occurred in the profile of mood states mood subscales of tension and fatigue between the baseline, prerace and postrace trials. Somatic anxiety was higher before the race compared with baseline measures. Discussion: RPE followed a linear progression of RPE during each discipline followed by a re-setting of the perception of effort at the start of the next discipline. The increase in RPE for the entire event followed a linear increase. The linear decline in run pace is consistent with a recent model in which expected RPE is used to modulate pacing. Anxiety and mood responses of participants in this study indicate that the emotional response of athletes before and after ultra-endurance exercise is closely aligned with their conscious thoughts.